The Superficial Anastomosing Veins of the Human Brain Cortex: A Microneurosurgical Anatomical Study - Tomasi, S. Ottavio; Umana, Giuseppe Emmanuele; Scalia, Gianluca; Raudino, Giuseppe; Graziano, Francesca; Palmisciano, Paolo; Priola, Stefano M.; Cappai, Pier Francesco; Capone, Crescenzo; Lawrence, Peter M.; Erös, Christian A.; Martin, Klaus D.; et al. (Frontiers in Surgery, 2022)
Introduction In this microneurosurgical and anatomical study, we characterized the superficial anastomosing veins of the human brain cortex in human specimens. Material and methods We used 21 brain preparations fixed in formalin (5%) that showed no pathological changes and came from the autopsy sections. The superficial veins were dissected out of the arachnoid with the aid of a surgical microscope. Results We dissected 9 female and 12 male brain specimens, with an average age of 71 ± 11 years (range 51-88 years). We classified the superficial veins in 5 types: I) the vein of Trolard as the dominat vein; II) the vein of Labbé as the dominant vein; III) a dominant sylvian vein group, and the veins of Trolard and Labbé nonexistent or only rudimentary present without contact to the Sylvian vein group.; IV) very weak sylvian veins with the veins of Trolard and Labbé codominant; and V) direct connection of Trolard and Labbé bypassing the Sylvian vein group. The vein of Trolard was dominant (Type I) in 21.4% and the vein of Labbé (Type II) in 16.7%. A dominant sylvian vein group (Type III) was found in 42.9%. Type IV and Type V were found in 14.3% and 4.7% respectively. Conclusion No systematic description or numerical distribution of the superior anastomotic vein (V. Trolard) and inferior anastomotic vein (V. Labbé) has been found in the existing literature. This study aimed to fill this gap in current literature and provide data to neurosurgeons for the practical planning of surgical approaches.